Analysis of GDP Per Capita, Population Density, and Number of Motor Vehicles on Environmental Quality in Indonesia - Atikah, Nisrina; Ramli; Rahman, Arif (Indonesian Journal Publisher, 2026)
Environmental quality is a critical issue faced by developing economies like Indonesia, which heavily rely on natural resource exploitation. This study analyzes the influence of GDP per capita, population density, and number of motor vehicles on environmental quality in Indonesia during 2012-2023. The research employs a descriptive quantitative approach using spatial panel data regression models. The Environmental Quality Index (ELI) serves as the dependent variable, while GDP per capita, population density, and number of motor vehicles constitute the independent variables. Secondary data were collected from the Central Statistics Agency (BPS) and the Ministry of Environment and Forestry. Results indicate that GDP per capita has a positive but insignificant effect on environmental quality (coefficient = 0.003737, p > 0.05). Population density exhibits a significant negative effect (coefficient = -0.073323, p < 0.05), and the number of motor vehicles shows a negative but insignificant effect (coefficient = -0.004381, p > 0.05). The Geographically Weighted Regression (GWR) analysis reveals spatial heterogeneity across provinces, with R-squared improving from 0.53 (global regression) to 0.81 (GWR model). These findings suggest that environmental quality determinants vary across regions, necessitating localized policy interventions for sustainable development.